The Self-Perceptions of Twice-Exceptional Children: A Systematic Review - Louise Küry; Christian Fischer (Education Sciences)
This systematic review examines the self-perceptions of twice-exceptional children. This review examines the self-concept, self-esteem and self-efficacy of these children, as well as the factors that influence their self-perceptions. The PRISMA guidelines were employed in the conduct of this systematic review. To be included in this study, articles had to be empirical, written in English and published in peer-reviewed journals, and be aligned with the research questions. A total of 18 papers were included for assessment of quality, the majority of which employed a case study design. The findings suggest that twice-exceptional children tend to perceive themselves in a negative manner. Furthermore, twice-exceptional children exhibited diminished global self-concept, accompanied by low self-esteem and self-efficacy. Positive factors influencing self-perception are adequate support from teachers and parents, early identification and strength-based support. A lack of understanding on the part of teachers and parents, insufficient attention to giftedness in and outside of school, and a sense of being different were identified as negative influencing factors. Further research is required to verify the results using a quantitative longitudinal study. The findings of this review highlight the necessity for adequate support and encouragement for twice-exceptional children, suggesting potential ways for their implementation.